Comparative genomic analysis of primary and synchronous metastatic colorectal cancers. - Sun Young Lee; Farhan Haq; Deokhoon Kim; Cui Jun; Hui-Jong Jo; Sung-Min Ahn; Won-Suk Lee (PLoS ONE, 2014)
Approximately 50% of patients with primary colorectal carcinoma develop liver metastases. Understanding the genetic differences between primary colon cancer and their metastases to the liver is essential for devising a better therapeutic approach for this disease. We performed whole exome sequencing and copy number analysis for 15 triplets, each comprising normal colorectal tissue, primary colorectal carcinoma, and its synchronous matched liver metastasis. We analyzed the similarities and differences between primary colorectal carcinoma and matched liver metastases in regards to somatic mutations and somatic copy number alterationss. The genomic profiling demonstrated mutations in APC(73%), KRAS (33%), ARID1A and PIK3CA (6.7%) genes between primary colorectal and metastatic liver tumors. TP53 mutation was observed in 47% of the primary samples and 67% in liver metastatic samples. The grouped pairs, in hierarchical clustering showed similar somatic copy number alteration patterns, in contrast to the ungrouped pairs. Many mutations (including those of known key cancer driver genes) were shared in the grouped pairs. The ungrouped pairs exhibited distinct mutation patterns with no shared mutations in key driver genes. Four ungrouped liver metastasis samples had mutations in DNA mismatch repair genes along with hypermutations and a substantial number of copy number alterations. Our results suggest that about half of the metastatic colorectal carcinoma had the same clonal origin with their primary colorectal carcinomas, whereas remaining cases were genetically distinct from their primary carcinomas. These findings underscore the need to evaluate metastatic lesions separately for optimized therapy, rather than to extrapolate from primary tumor data.